Applying nominal expenditure rules in the euro area - Clemens Fuest; Daniel Gros (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
In the debate on euro area fiscal governance, the current deficit rules of the EU have repeatedly been criticised to have a pro-cyclical effect, leading to overly lax fiscal policies in good times and a too restrictive regime in bad times. An analysis by EconPol researchers Clemens Fuest (ifo) and Daniel Gros (CEPS) shows that most major EU countries are over-spending at a level not compatible with spending rules for sustainable public finances.
Keywords: 330